You can stop stupid stopping losses from accidental and malicious actions - Winkler, Ira; Brown, Tracy Celaya (Gildan Media, 2021)
Around the world, users cost organizations billions of dollars due to simple errors and malicious actions. They believe that there is some deficiency in the users. In response, organizations believe that they have to improve their awareness efforts and making more secure users. This is like saying that coal mines should get healthier canaries. The reality is that it takes a multilayered approach that acknowledges that users will inevitably make mistakes or have malicious intent, and the failure is in not planning for that. It takes a holistic approach to assessing risk combined with technical defenses and countermeasures layered with a security culture and continuous improvement. Only with this kind of defense in depth can organizations hope to prevent the worst of the cybersecurity breaches and other user-initiated losses. Using lessons from tested and proven disciplines like military kill-chain analysis, counterterrorism analysis, industrial safety programs, and more, Ira Winkler and Dr. Tracy Celaya's You CAN Stop Stupid provides a methodology to analyze potential losses and determine appropriate countermeasures to implement. Business technology and security professionals will benefit from the information provided by these two well-known and influential cybersecurity speakers and experts.
Online resource; title from title details screen (OverDrive, viewed July 26, 2021)
Keywords: Business enterprises -- Security measures; Computer security; Entreprises; Sécurité; Mesures; Sécurité informatique; Business enterprises; Security measures; Downloadable audio books; Audiobooks; Livres audio